Assessment of airflow and heat transfer around a thermal manikin in a premise served by DOAS and ceiling fans. (15th April 2022) - Hasama, Takamasa; Mihara, Kuniaki; Sekhar, Chandra; Cheong, Kok Wai David; Tham, Kwok Wai
Abstract: Ceiling fan improves thermal comfort and reduces air-conditioning energy consumption in super low energy buildings operated at warmer room air temperature with increased air movement. This paper investigated the characteristics of airflow generated by the ceiling fans around a thermal manikin body, and the convective heat transfer caused by the airflow distribution through experiment and CFD for standing and seated postures. The standing and seated postures showed almost the same convective heat transfer for the whole-body, but the contribution of mean velocity and turbulence components were different. Turbulence intensity (median value and dispersion) of the seated posture was higher, and the dispersion range reaches between 20 and 84% despite the average velocity being relatively low compared to the standing posture when the fan speed exceeds 100 rpm. The convective heat transfer coefficient for the whole-body caused by the ceiling fan was 32–75% of the horizontal air flow cases of previous studies at inflow air speed under 1.1 m/s for both postures. On the other hand, under ceiling fan flow the heat transfer coefficient at the lower body of the manikin remains relatively low compared to horizontal flow even at increased fan speeds. This difference potentially leads to a different thermal sensation in corresponding body parts between the ceiling fan flow and the horizontal flow situations. Highlights: k- ω SST RANS predicts whole-body total heat transfer of thermal manikin under ceiling fan with 5–12% of APE. Standing and seated postures show almost same whole-body convective heat transfer under ceiling fan but contribution of mean velocity and turbulence components are different. Whole-body convective heat transfer coefficient under ceiling fan is 32–75% of horizontal air flow under 1.1 m/s inflow. Heat transfer coefficient under ceiling fan remains relatively low at lower manikin body parts compared to horizontal flow.